The statehood of ‘collapsed’ states in Public International Law - Moscoso de la Cuba, Pablo (Pontificia Universidad Católica del Perú. Fondo Editorial, 2011)
Over the last few years the international community has been witnessing a phenomenon commonly referred to as ‘State failure’ or ‘State collapse’, which has featured the disintegration of governmental structures in association with grave and intense internal armed conflicts, to the point that the social organization of society what international law considers the government of the State, a legal condition for statehood – has almost, or in the case of Somalia totally, disappeared from the ground.
Keywords: Estudios internacionales; https://purl.org/pe-repo/ocde/ford#5.09.01